Medication adherence and its influencing factors in postoperative thyroid cancer patients: a cross-sectional study - Li, Wen; Yu, Luxin; Zheng, Hui; Kim, Geok Soh; Kim, Lam Soh (John Wiley and Sons, 2025)
Background: Medication adherence is critical for the recovery of patients after thyroid cancer surgery. Therefore, this study investigated the current medication adherence status in Chinese postoperative thyroid cancer patients and analysed the influencing factors.